Model Kepemimpinan Berbasis Nilai Islam dalam Menjawab Tantangan Keorganisasian Pendidikan Abad Ke-21 - Ardyanto Ardyanto; Abdul Wahid Wandana; Ahmad Bayhaqi; Much Hasan Darojat; Samiyono Samiyono; Maya Yunus (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2026)
Educational leadership in the twenty-first century faces increasingly complex organizational challenges, including globalization, technological disruption, rising demands for educational quality, and the weakening of moral and character values in institutional practices. These conditions require a leadership model that is not only oriented toward managerial effectiveness but also grounded in moral and spiritual values. This article aims to examine and formulate an Islamic values-based leadership model as a response to organizational challenges in contemporary educational institutions. This study employs a qualitative approach using a library research design. Primary data sources include the Qur’an and Hadith, while secondary data are derived from scholarly books, journal articles, and relevant previous studies on Islamic leadership and educational management. Data analysis was conducted through descriptive-analytical methods, including data reduction, concept categorization, and interpretative analysis. The findings indicate that fundamental Islamic leadership values—such as trustworthiness (amanah), justice, deliberation (shura), responsibility, and exemplary conduct—are highly relevant in addressing modern educational organizational challenges. The implementation of these values contributes to strengthening institutional vision, improving the quality and effectiveness of decision-making, fostering an ethical and healthy organizational culture, and supporting the holistic and sustainable development of students’ character. This article concludes that Islamic values-based leadership constitutes a strategic and applicable alternative for managing Islamic educational institutions in the face of twenty-first-century complexities